Kontinuität im Wandel der Zeit. Deutsches Kalenderschrifttum um die Wende zum 20. Jahrhundert in der Provinz Posen - Skalska, Magdalena (Studia Germanica Posnaniensia, 2013)
Continuity in changing times. The German calendar literature by the turn of the 20th century in the Province of Poznań Calendars were originally developed for the purpose of temporal orientation and coordination of activities of a group of people. Over time, they have been used as an important means of forming opinions. In regards to that, one cannot underestimate the role of narrative text forms which have been present in calendars since the 16th century and gradually grew in size and importance. The composition of a wide variety of text types and the combination of text and illustration were responsible for the mass distribution of such publications in the 19th century. In the Province of Poznań calendars also enjoyed great popularity. Of special interest is the Evangelical People’s Calendar, which was published in Poznań for around 80 years (1861–1941). It accompanied the German population in this area through the major transition points from the end of the 19th to the beginning of the 20th century. In relation to the German calendar literature of the Poznań area, the following questions will be investigated in this article: which turning points of the 20th century were included in the calendar? Which events were considered epochal by the calendar makers? In which form were they presented in the calendars? What was the role of the historical-political and socio-mental context? How was the potential of calendars used to give the readers the sense of continuity and stability by the turn of the century?